Evaluasi Program Pelatihan In House Training (IHT) di Sekolah Dasar Swasta - Ayuningtyas, Aih Ervanti; Slameto, Slameto; Dwikurnaningsih, Yari (Universitas Kristen Satya Wacana, 2017)
The purpose of this study is to evaluate the instructional, institutional, and behavioral dimensions of the In-House Training (IHT) program at the SD Muhammadiyah (Plus) Salatiga Academic Year 2013/2014. This is an evaluative study with Three Dimensional Cube Model. Data collection techniques used interviews, questionnaires, and document studies. Collected data then analyzed descriptively, ordinal data were analyzed using Three Box Method. Validation of data using technique and/or source triangulation. The results showed: (1) In the instructional dimension including organization, content/material, methodology, facilities, and cost included in good category, although there is little improvement in adjusting method with program objectives; (2) In the institutional dimension that includes speakers, trainees, administrator/committees, education specialists, families, and communities are included in either category, although there is still need for improvement in terms of needs analysis in terms of the needs of teachers; (3) In the behavioral dimension that is the goal of the IHT program and is divided into the cognitive, affective, and psychomotor domains almost all have been achieved well, although there is one goal in the psychomotor realm that has not been achieved well because one goal is not a priority to be achieved in time of three years. Recommendations for program sustainability, programs can be continued with improvements.